The Evaluation of Implementation Strengthening Character Education's Program at Junior High School in Sorong Regency - Heny Sri Astutik; Roni Andri Pramita (Universitas Tidar, 2023)
Strengthening Character Education (PPK) is one of the Nawacita points that was proclaimed so that the national character education process must be carried out actively by education providers in developing the learning process by carrying out the process of internalization and appreciation of the character values ​​reflected in the curriculum. This research aims to determine teachers' understanding regarding the Strengthening Character Education program, implementation, and results of the PPK program in mathematics subjects at Sorong Regency Middle Schools, Southwest Papua, Indonesia. This was evaluation research using Stake’s Countenance Evaluation Model. The research subjects were all junior high school teachers and students in Sorong Regency. The research sample was determined using the purposive sampling technique. Three schools were selected from all junior high schools in Sorong Regency, one each with A, B, and C accreditation, with a total sample of 695 consisting of 648 students and 47 teachers. The evaluation of program implementation was reviewed based on teachers' understanding, implementation, and results of implementing the PPK program. Data collection was carried out through documentation, interviews, and questionnaires. The study showed that 1) teachers' understanding and planning regarding the PPK in mathematics subjects is in the good category; and 2) the implementation of the PPK in mathematics subjects is still not running optimally. These results can be used to recommend improvements to the character education program.